Konsep Kepemilikan Ekonomi Islam Materi Fiqh Kelas XII (Implikasinya Terhadap Pendidikan Agama Islam untuk Menanggulangi Pengangguran) - Rahmat Rahmat; Muhammad Husnur Rofiq (Nazhruna: Jurnal Pendidikan Islam, 2018)
Humans naturally tend to have fun, and love for many wives, children and possessions. This has been described by Allah Almighty in His Word, Surah Al Imran verse 14; "It is made to feel beautiful in the human view of love for what is desired, in the form of women, children, accumulated property in the form of gold and silver, selected horses, farm animals and fields. That is the pleasure of living in the world, and beside Allah is a good place to return ". This verse, can be interpreted as an explanation that the tendency towards pleasure is indeed the nature of man. Therefore, it is certain that he is motivated to try to be rich and so forth. Whereas banning this natural urge is a violation both in the eyes of Islam and applicable law. As for Islam, it has regulated how humans obtain wealth according to the level of needs and abilities and how they use it so that their wealth will be useful for religion, the world.